The DISCOVER Trial: Application of the Karius Plasma Next-Generation Sequencing Test for Pathogen Detection in Stem-Cell Transplant Patients. (4th October 2017) - Fung, Monica; Seng, Hon; Hollemon, Desiree; Hong, David; Blauwkamp, Tim; Kertesz, Mickey; Dolan, Estelle; Eng, Jamie; Wong, Kathy; Logan, Aaron; Chin-Hong, Peter
Abstract: Background: The diagnosis of infections in stem-cell transplant (SCT) patients is challenging. There is a need for improved diagnostics that can quickly and accurately detect a broad range of viruses, bacteria, and fungi that can infect these patients to guide targeted therapy. Methods: We enrolled 20 patients in a prospective study evaluating the Karius plasma next-generation sequencing (plasma NGS) test to detect infections in SCT patients. Patients had baseline plasma samples drawn prior to transplant followed by weekly collections during engraftment and at onset of febrile episodes. Samples were transferred to the Karius CLIA/CAP laboratory (Redwood City, CA) where cell-free DNA was extracted from plasma and NGS performed. Human sequences were removed and remaining reads were aligned against a curated pathogen database. Organisms present at a significance level above a predefined threshold were reported. Results: Cytomegalovirus (CMV) was identified in 12/20 patients. Using a nearest-neighbor method, 61 pairs of observations were identified for a comparison of plasma NGS and CMV qPCR collected within 1 day of each other. Positive agreement (PPA) between plasma NGS and CMV qPCR was 84.1% (37/44). PPA was 100% (20/20) when values below the lower limit of quantitation (<137 IU/ml) for CMV qPCR were excluded. In addition to CMV, plasma NGS detected EBV, HHV6B, BK virus and Torque teno viruses. Plasma NGS also detected pathogens prior to conventional tests being ordered in two patients with subsequently confirmed acute infections; Staphylococcus aureus was detected one day prior to blood culture in one patient and Chlamydia trachomatis 30 days prior to targeted testing in a second patient. These two cases highlight the potential of plasma NGS to detect pathogens in SCT patients early when used as a monitoring tool. Conclusion: Karius has developed a novel NGS plasma test that can simultaneously identify pathogens in SCT patients. The test had 100% concordance with CMV qPCR above the lower level of quantitation. Further work is ongoing to determine the lower limits of detection for the plasma NGS test. Using NGS to monitor SCT patients for infection could permit earlier detection of pathogens, enabling earlier targeted therapy for this vulnerable population. Disclosures: H. Seng, Karius, Inc: Employee,  Salary; D. Hollemon, Karius, Inc: Employee,  Salary; D. Hong, Karius, Inc.: Collaborator, Research support and Salary;  T. Blauwkamp, Karius, Inc: Employee,  Salary; M. Kertesz, Karius, Inc: Employee,  Salary; J. Eng, Karius, Inc.: Collaborator,  Salary; K. Wong, Karius, Inc.: Collaborator,  Salary; P. Chin-Hong, Karius, Inc.: Collaborator, Research support